Prevalence of excessive screen time and TV viewing among Brazilian adolescents: a systematic review and meta-analysis - Camila W. Schaan; Felipe V. Cureau; Mariana Sbaraini; Karen Sparrenberger; Harold W. Kohl III; Beatriz D. Schaan (Elsevier, 2019)
Purpose: To evaluate the prevalence of excessive screen-based behaviors among Brazilian adolescents through a systematic review with meta-analysis. Data source: Systematic review and meta-analysis were recorded in the International Prospective Register of Ongoing Systematic Reviews (PROSPERO-CRD 2017 CRD42017074432). This review included observational studies (cohort or cross-sectional) that evaluated the prevalence of excessive screen time (i.e. combinations involving different screen-based behaviors) or TV viewing (≥2 h/day or >2 h/day in front of screen) through indirect or direct methods in adolescents aged between 10 and 19 years. The research strategy included the following databases: MEDLINE, LILACS, SciELO and ADOLEC. The search strategy included terms for "screen time", "Brazil", and "prevalence". Random effect models were used to estimate the prevalence of excessive screen time in different categories. Data summary: Twenty-eight out of 775 studies identified in the search met the inclusion criteria. The prevalence of excessive screen time and TV viewing was 70.9% (95% CI: 65.5-76.1) and 58.8% (95% CI: 49.4-68.0), respectively. There was no difference between sexes in both analyses. The majority of studies included showed a low risk of bias. Conclusions: The prevalence of excessive screen time and TV viewing was high among Brazilian adolescents. Intervention are needed to reduce the excessive screen time among adolescents. Resumo: Objetivo: Avaliar a prevalência de tempo excessivo de tela e de TV em adolescentes brasileiros através de revisão sistemática com meta-análise. Fontes de dados: A revisão sistemática e a meta-análise foram registradas no o inglês (não tem tradução para português): International Prospective Register of Ongoing Systematic Reviews (PROSPERO-CRD 2017 CRD42017074432). Esta análise incluiu estudos observacionais (coorte ou transversais) que avaliaram a prevalência de tempo excessivo de tela (ou seja, combinações que envolvem diferentes comportamentos baseados em tempo de tela) ou tempo em frente à TV (≥ 2 horas/dia ou > 2 horas/dia em frente à tela) por avaliação direta ou indireta em adolescentes com idades entre 10 a 19 anos. A estratégia de pesquisa incluiu as seguintes bases de dados: MEDLINE, LILACS, SciELO e ADOLEC. A estratégia de busca incluiu termos como "tempo de tela", "Brasil" e "prevalência". Os modelos de efeito aleatório foram utilizados para estimar a prevalência de tempo excessivo de tela em diferentes categorias. Resumo de dados: 28 dos 775 estudos identificados na busca atenderam aos critérios de inclusão. A prevalência de tempo excessivo de tela e tempo de TV foi 70,9% (IC de 95%: 65,5 a 76,1) e 58,8% (IC de 95%: 49,4 a 68,0), respectivamente. Não houve nenhuma diferença entre os sexos nas duas análises. A maior parte dos estudos incluídos mostrou baixo risco de viés. Conclusões: A prevalência de tempo excessivo de tela e tempo de TV foi alta entre os adolescentes brasileiros. São necessárias intervenções para reduzir o tempo excessivo de tela entre os adolescentes. Keywords: Sedentary lifestyle, Adolescent, Meta-analysis, Palavras-chave: Estilo de vida sedentário, Adolescente, Meta-análise